2017
DOI: 10.1021/acsami.7b09710
|View full text |Cite
|
Sign up to set email alerts
|

Guiding the Growth of a Conductive Filament by Nanoindentation To Improve Resistive Switching

Abstract: Redox-based memristor devices, which are considered to have promising nonvolatile memory, mainly operate through the formation/rupture of nanoscale conductive filaments. However, the random growth of conductive filaments is an obstacle for the stability of memory devices and the cell-to-cell uniformity. Here, we investigate the guiding effect of nanoindentation on the growth of conductive filaments in resistive memory devices. The nanoindented top electrodes generate an electric field concentration and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 33 publications
4
84
0
2
Order By: Relevance
“…C-AFM enables the direct writing of nanofilaments by precisely defining the nucleation sites, yielding more uniform nucleation and growth. [18,19] Using an automated script, nanofilament formation events at hundreds of xy locations on the film are recorded as a function of applied bias. This spatially dense sampling allows us to fully capture the stochasticity of nanofilament growth and enables statistical analyses of the data, which are particularly crucial for a polymer electrolyte containing microscopic heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…C-AFM enables the direct writing of nanofilaments by precisely defining the nucleation sites, yielding more uniform nucleation and growth. [18,19] Using an automated script, nanofilament formation events at hundreds of xy locations on the film are recorded as a function of applied bias. This spatially dense sampling allows us to fully capture the stochasticity of nanofilament growth and enables statistical analyses of the data, which are particularly crucial for a polymer electrolyte containing microscopic heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…To make atomic scale devices practical, a path toward a more reproducible technology providing devices with a high endurance is needed. And indeed, geometry engineering has already shown promise toward this goal [20][21][22][23] . Researchers already demonstrated that they could lower the mean switching voltages from 1.11 to 0.27 V and improve the cycle-to-cycle variance when transitioning from a flat to a tip-like electrode shape 21 .…”
mentioning
confidence: 99%
“…Управление воспроизводимостью мемристивного эффекта может быть осуществлено путем формирования специальных концентраторов электрического поля [2], определяющих параметры проводящих каналов (филаментов), с разрушением и восстановлением которых связано резистивное переключение, а также путем выбора (инженерии) материалов в мемристивной структуре [3,4]. Используется также адаптивное программирование резистивного состояния путем коррекции параметров переключающих импульсов напряжения в зависимости от результата программирования [5][6][7].…”
Section: Introductionunclassified